Are you a budding academic writer?. (March 2016) - Grant, Maria J.; Bonnett, Penny; Sutton, Anthea; Marshall, Audrey; Murphy, Jeannette; Spring, Hannah
Abstract: Academic writing can seem a daunting prospect although with the right support and information it can be more achievable than you think. In this first set of editorial comments of 2016, editors from all sections of the Health Information and Libraries Journal outline the origins of the individual section of the journal which they oversee and highlight some of the things you might want to consider when thinking of submitting your writing for publication.